The association between gastric cancer and sarcopenia: a scoping review - Wang, Xue; Sun, Xuefeng; Wu, Yuanyu; Wang, Yanjun; Ren, Jingyi; Fang, Xuedong (Frontiers in Oncology, 2025)
AimTo explore the relationship between gastric cancer and sarcopenia and review the underlying mechanisms.MethodA systematic search was conducted across the Web of Science, PubMed, Cochrane, CNKI, Wanfang, and VIP databases following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines. Literature describing the relationship between gastric cancer and sarcopenia was included in this study, with methodological quality assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools.ResultsAmong the 1,518 identified publications, 33 cohort studies involving 10,679 participants were ultimately included. The results revealed a sarcopenia prevalence ranging from 6.8% to 72.22% in gastric cancer patients. Most studies indicated that reduced muscle mass—potentially attributable to fat infiltration, immunosuppression, cachexia-associated metabolic disturbances, and protein reserve depletion—serves as an independent predictor of postoperative complications, overall survival, and disease-free survival in gastric cancer patients. However, due to heterogeneity in assessment criteria and measurement tools, only two studies demonstrated that sarcopenia did not significantly impact survival or prognosis in this population.ConclusionPostoperative sarcopenia exhibits a high prevalence after gastric cancer surgery and is a significant predictor of adverse clinical outcomes. This underscores the importance of prioritizing muscle mass preservation in postoperative management and integrating its assessment into preoperative risk stratification. However, the current body of evidence is limited by inconsistent diagnostic criteria and a lack of mechanistic studies. Future research should focus on establishing standardized diagnostic frameworks through multidisciplinary collaboration and developing targeted interventions to improve patient prognosis.